2017
DOI: 10.5937/jpea1704192k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of energy consumption in the convective and freeze drying of raspberries

Abstract: Freeze-drying has proven to be one of the best drying processes thus far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Only in the case of VD and AD, a statistically significant but slightly shorter DT was observed for GR compared to WH. Other authors also observed that FD takes much longer than other drying methods [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only in the case of VD and AD, a statistically significant but slightly shorter DT was observed for GR compared to WH. Other authors also observed that FD takes much longer than other drying methods [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The downside of this method is that it is one of the most energy‐demanding technologies with high production costs . Kešelj and coworkers discovered that freeze‐drying of raspberry requires 1.9 times more energy than convective drying . This is one of the reasons why scientific research has been focused on combining different drying technologies in order to achieve good quality and lower production costs …”
Section: Introductionmentioning
confidence: 99%
“…19 Kešelj and coworkers discovered that freeze-drying of raspberry requires 1.9 times more energy than convective drying. 20 This is one of the reasons why scientific research has been focused on combining different drying technologies in order to achieve good quality and lower production costs. 5,21,22 Stamenkovi c and coworkers showed that the convectively dried Polana raspberry variety, which is used as addition to some confectionery products, biscuits, cookies, dairy product, etc, may be an adequate substitution for a freeze-dried raspberry with the right choice of drying factors.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, the equipment of freeze drying comes with a high maintenance cost 10 and the energy consumption is approximately twice than the convective drying. 11 Vacuum drying is also reported to have positive effects on quality compared with the hot air convective drying, but the energy consumption is increased at a similar scale. 12 As for the fluidized bed drying (FBDs), it is reported that quality loss of medicinal plant drying was limited, compared with hot air and solar drying.…”
mentioning
confidence: 99%
“…17,18 Due to the high drying efficiency, FBD is well-suited for large scale operations. 19,20 It is also an economical method compared to vacuum, 12,21 hybrid, 3,8,21 freeze 10,11,21 and convective drying. 14,21 Generally, FBDs are more convenient and attractive in industry, even for farmers, to produce high-quality products.…”
mentioning
confidence: 99%